China’s digital economy development: incentives and challenges - Chen, Yang; Xu, Shaorui; Lyulyov, Oleksii; Pimonenko, Tetyana (Technological and Economic Development of Economy, 2023)
The development of the digital economy has become a new way to respond to the epidemic impact effectively. With the innovative breakthrough of information and communication technology, the digital and real economies are deeply integrated. The digital economy has become an important driving force for the transformation of economic momentum and development. Panel data from 31 provinces in China from 2010 to 2019 were selected for analysis. In the first stage, the study constructed the evaluation index system of digital economy development. Then, the quality development index of the digital economy is calculated by using the entropy method. Finally, the main factors of digital economy development are analysed by spatial measurement. The research results prove that: (1) the development of China’s digital economy in 2010–2019 has gradually increased; (2) the development of the digital economy has a positive correlation between regions and has a spatial spillover effect; (3) the level of economic development, urbanisation, government support, industrial structure, and the level of opening will promote the development of the digital economy. First published online 30 November 2022